PENINGKATAN KETERAMPILAN PROSES SAINS DAN KETERAMPILAN SOSIAL SISWA MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS BERBASIS EKSPERIMEN (UPEJ Unnes Physics Education Journal, 2013)
The student’s cognitive learning outcomes on the physics subject are still low. This indicates student’sscience process skills and social skills are still low. Therefore, an effort to improve student’s skill of scienceprocess and social process will be carried out by implementing the STAD cooperative learning model based onexperiment. The method was a class action research that conducted in three cycles. The observation sheets andwork sheets were used to observe the science process skills, while attitude scale questionnaires were used toobserve the social skills. The improvement from one cycle to the next cycle can be determined by using gain test(g). The result of classical achievement of science skills process in the cycle I was 36,67%, in the cycle II was90,00%, and in the cycle III was 96,67 %. The result of the classical achievement of the social skills in the firstlesson was 50,00% and 60,00% at the end of the lesson. The result of the achievement of the classical cognitiveaspect in the cycle I was 33,33%, in the cycle II was 63,33% and 86,67% in the cycle III. Therefore, it can beconcluded that the implementation of the STAD type cooperative learning can improve the science processskills, social skills, and the student’s learning outcomes.